The Determinants of Capital Structure: A Comparative Study between Sharia and Non-Sharia Manufacturing Companies in Indonesia Stock Exchange (IDX) - Imam Akbar Ilham Arif; Muhammad Umar Mai (Politeknik Negeri Bandung, 2020)
Every company has a long-term goal to maximize the value of the company, which also means to maximize the prosperity of its shareholders. One of the ways to achieve this goal is to determine the optimal capital structure. The optimal capital structure allows the company to bear the low average cost of the capital. Therefore, the decision of capital structure is one of the most important decisions.Go public manufacturing companies in Indonesia Stock Exchange are divided into two groups; the sharia and non-sharia companies. Sharia companies, including the sharia manufacturing ones, have specific rule in the use of funds as the company capital. The rule states that the maximum use of usury-based debt is by 45%. At the same time, the theories about capital structure and research results support the use of debt as the main source of funds. This study used data obtained from the Indonesian Capital Market Directory and Summary of Company Performance for the period of 2011-2017. They were analyzed by using panel data for multiple regression analysis and difference tests. The results show significant differences between sharia and non-sharia manufacturing companies with a probability of 0,000. Moreover, almost all determinant factors such as Size, Tangibility, Profitability, and Gross Domestic Product have significant effects on Book Leverage as an indicator of Capital Structure for both groups of companies.